2018
DOI: 10.1101/251843
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

nNOS-expressing neurons in the ventral tegmental area and substantia nigra pars compacta

Abstract: 20GABA neurons in the ventral tegmental area (VTA) and substantia nigra pars compact (SNc) 21 play key roles in reward and aversion through their local inhibitory control of dopamine 22

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…For this paper, we focus on the midline VTA, which contains GABA (VTA Vgat ) and glutamate/nitric oxide synthase (VTA Vglut2 ) neurons 23,32,33 . These VTA Vgat and VTA Vglut2/NOS1 neurons inhibit and excite, respectively, the dopamine cells, but also, by projecting out of the VTA, exert effects independent of dopamine 23 .…”
Section: Introductionmentioning
confidence: 99%
“…For this paper, we focus on the midline VTA, which contains GABA (VTA Vgat ) and glutamate/nitric oxide synthase (VTA Vglut2 ) neurons 23,32,33 . These VTA Vgat and VTA Vglut2/NOS1 neurons inhibit and excite, respectively, the dopamine cells, but also, by projecting out of the VTA, exert effects independent of dopamine 23 .…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, we performed DARPP‐32 and nNOS (neuronal nitric oxide synthase) immunohistochemistry in VTA (Figure B,C). nNOS is expressed in a subset of interneurons in the VTA . Interestingly, we found some colocalization of DARPP‐32 and nNOS in VTA as indicated by the white arrowheads (Figure C).…”
Section: Resultsmentioning
confidence: 65%
“…Remarkably, a study showed that neuronal nitric oxide synthase (nNOS) is also another marker of interneurons in VTA. nNOS was identified as a marker of VTA GABA interneurons that is not expressed in VTA DA neurons, and putatively expressed in glutamatergic projecting neurons, mostly in the rostral linear nucleus of the raphe (RLi) . Although, glutamatergic neurons represent only 2%‐3% of total VTA neurons .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, cell‐type specific virus‐based anterograde tracing in mice has shown that PBP and SNc GABAergic neurons expressing nNOS do not make any detectable projection outside their residing area and thus appear to be interneurons (Paul et al, 2018). In contrast, the glutamatergic nNOS‐expressing neurons of the RLi have been shown to project to a number of regions, including the LHA, the ventral pallidum, and the median raphe nucleus (Paul et al, 2018). Interestingly, a study from 2019 showed that the chemogenic activation of the subset of glutamatergic neurons of the VTA expressing nNOS projecting to the LHA has wake‐promoting effects, while the activation of the GABAergic neurons of the VTA‐PBN expressing nNOS did not induce either sleep or wakefulness (X. Yu et al, 2019).…”
Section: Anatomical Distribution and Phenotypic Diversity Of Nos Neurmentioning
confidence: 99%
“…In the midbrain, while nNOS-expressing neurons in the PBP part of the VTA and the SNc appear to be GABAergic, nNOS neuron in the RLi of the VTA have been shown to be mostly glutamatergic (Paul et al, 2018;X. Yu et al, 2019).…”
Section: Phenotypic Heterogeneity Of Nnos Neuronsmentioning
confidence: 99%